On the study of teardrop shaped split and collision (TS-SAC) micromixers with balanced and unbalanced split of subchannels. (2nd January 2022) - Gidde, Ranjitsinha
ABSTRACT: A teardrop-shaped split and collision (TS-SAC) micromixer based on the concept of balanced/unbalanced splits and collisions of fluid streams is presented. Numerical study is carried out for Reynolds numbers in the range of 0.1–75. In-depth flow and mixing dynamics for the micromixers are studied to assess mixing performance qualitatively. In order to produce unbalanced collision of the two fluid streams, difference in mass flow rate in the two sub-channels is utilized. The performance characteristics, viz., mixing index, pressure drop, mixing cost and mixing sensitivity are used to study mixing performance. A significant effect of unbalanced collisions of the fluid streams on the mixing enhancement is observed. Micromixer shows interesting mixing dynamics for different ratios sub-channels widths. A high mixing index and a low-pressure drop are observed for the micromixer with highest ratio of the widths of sub-channels. However, a low mixing index and a high-pressure drop are observed for the micromixer with lowest ratio of the widths of sub-channels.